U-Drive: UTHM Car Rental System for University Student (ANDROID) - Shahnizam, Ahmad Syazwan; Noor Zuraidin Mohd Safar (Applied Information Technology And Computer Science, 2025)
The U-Drive UTHM Car Rental System is designed to address the transportation challenges encountered by students at Universiti Tun Hussein Onn Malaysia (UTHM), such as the high costs, restricted accessibility, and inefficiencies of traditional rental options. The system’s goal is to offer a mobile car rental solution that is efficient and user-friendly. Real-time vehicle availability, GPS tracking, flexible reservation options, and contactless payment integration through Card and E-Wallet are all included in this solution. Additionally, it is designed to be cost-effective. Iterative design, development, and testing processes were facilitated by the Agile methodology, which was developed using the Flutter framework as the development platform and the Dart programming language, in conjunction with Firebase for real-time data synchronization, to ensure scalability, security, and Usability. Car-sharing practices can considerably improve transportation accessibility, fleet management for administrators, and alignment with sustainability objectives, according to key findings. The study emphasizes the potential for analogous scalable solutions in future research and should investigate any supplementary improvements, such as integrating advanced analytics for fleet optimization and electric vehicle options.